PENGARUH KONDISI KEUANGAN, DEBT DEFAULT, KUALITAS AUDIT DAN UKURAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Indriani Dwie Riefni; Hardi Hardi; Hariyani Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of financial conditions, debt default, audit quality and company size on going concern audit opinion acceptance. The population of this study is publicly traded companies listed on the Indonesian Stock Exchange (BEI) in the 2013-2017 period. The research sample was selected using purposive sampling method. Data is obtained through data from the official website of the Indonesia Stock Exchange and other related websites as well as by studying literature related to research problems, both print and electronic media. The data analysis techniques used in this study were descriptive statistics and logistic regression. Financial condition variables affect going concern audit opinion with a significance level of 0.017 which is greater than (5%) or 0.017 <α = 0.05, debt default affects going concern audit opinion with a significance level of 0.000 that is greater than (5%). ) or 0.000 <α = 0.05, audit quality has no effect on going concern audit opinion with a significance level of 0.469 which is smaller than (5%) or 0.469> α = 0.05, and company size affects going concern audit opinion with a significance level of 0.000 which is smaller than (5%) or 0.000 <α = 0.05Keywords: Financial Condition, Debt Default, Audit Quality and Company Size